Association of serum selenium and inflammatory markers in patients with knee osteoarthritis - Farshad Amirkhizi; Soudabeh Hamedi-Shahraki; Mehran Rahimlou (Nutrition and Health, 2026)
Background Selenium (Se), an essential trace element with antioxidant and anti-inflammatory properties, may play a protective role in mitigating inflammation in osteoarthritis (OA). Aims This study investigates the association between serum Se concentrations and key inflammatory markers in patients with knee OA. Methods A cross-sectional study was conducted involving 151 individuals diagnosed with mild-to-moderate knee OA, recruited from hospitals and private clinics. Serum Se concentrations were measured using hydride generation atomic absorption spectrophotometry. Inflammatory markers, including interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), nuclear factor-kappa B (NF-κB) p65, and matrix metalloproteinases (MMPs) (MMP-1 and MMP-3), were quantified using enzyme-linked immunosorbent assays. Results The mean serum Se concentration was 58.5 ± 11.7 μg/L. Higher serum Se levels were significantly associated with lower concentrations of IL-6 ( β = −0.13, 95% confidence interval (CI): −0.21 to −0.05, P = 0.002), TNF-α ( β = −0.14, 95% CI: −0.24 to −0.04, P = 0.009), NF-κB p65 ( β = −0.01, 95% CI: −0.02 to −0.002, P = 0.013), and MMP-3 ( β = −0.07, 95% CI: −0.13 to −0.01, P = 0.020). No significant associations were found between serum Se levels and IL-1β, high-sensitivity C-reactive protein, or MMP-1. Conclusion Higher serum Se concentrations were inversely associated with several inflammatory markers, including IL-6, TNF-α, NF-κB p65, and MMP-3, suggesting a potential protective role of Se in reducing inflammation in knee OA. Further longitudinal and interventional studies are needed to confirm these findings and explore the therapeutic potential of Se in OA management.